Circulation of Herpesvirus and Alphatorquevirus DNA in each trimester in asymptomatic women pregnant with twins - Tania Regina Tozetto-Mendoza; Layla Honorato; Mariane Pereira Brito; Noely Evangelista Ferreira; Iara M. Linhares; Angela Silvano; Antonio Charlys da Costa; Silvia Helena Lima; Viola Seravalli; Mariarosaria Di Tommaso; Maria Cassia Mendes-Correa; Steven S. Witkin (PLoS ONE, 2025)
Background Data on the dynamics of Herpesviruses and Torque teno virus (TTV) in plasma from twin pregnancies are limited, despite their potential to provide insights into maternal immune status in this high-risk population. Methods A convenience sample of plasma was obtained from 54 healthy women with twin pregnancies and no adverse outcomes. The plasma samples were collected at 8–15, 17–25, and 26–35 weeks of gestation at Careggi University Hospital, Florence, Italy. Real-time PCR detected Herpesviruses and TTV DNA, determined viral titers, and evaluated associations with cytokine levels and pregnancy-related parameters. Results Herpesvirus were detected in 10 women (18.5%): three for herpes simplex virus (HSV)-1, three for human herpesvirus (HHV)-6, one for both HSV-1 and HHV-6, and one each for HSV-2, cytomegalovirus (CMV), or Epstein–Barr virus (EBV). Only one woman was positive throughout all trimesters (HHV-6). TTV DNA was detected in 42 women (77.7%), persistently in 26 (48.1%) and transiently in 16 (29.6%). No associations were found between viral detection and plasma interleukin (IL)-1β, IL-6, tumor necrosis factor-α (TNF-α), or pregnancy-related parameters, except for a higher prevalence of TTV in women with previous deliveries (p = 0.0402). Conclusion The high frequency and variable viral titer of TTV with the transient circulation of some herpesviruses appear unaffected by the immunological adaptations inherent to this setting of twin pregnancies without adverse outcomes, as supported by the absence of correlation between inflammatory markers and viral dynamics. Nonetheless, ongoing monitoring of obstetric and postnatal outcomes remains warranted.